Pemantauan Parameter Panel Surya Berbasis Arduino secara Real Time - Muhammad Rizal Fachri; Ira Devi Sara; Yuwaldi Away (Jurnal Rekayasa Elektrika, 2015)
Monitoring the output parameters of a solar module is required for assessing its performance under real operating conditions. This paper presents a new technique for monitoring the output parameters i.e. current and voltage of solar module directly under real operating conditions. In this new monitoring technique, the output parameters of a solar module can be directly processed in real time condition and their results are displayed in a graph. The monitoring system is developed using microprocessor Arduino Atmega 328P and equipped with calibrated current and voltage sensors, a data acquisition system which is integrated directly into an Excel spreadsheet using the PLX-DAQ application program and a memory card for backup. The monitoring system is connected to a computer using a RS232 serial port. The collected data is saved directly into a spreadsheet and plotted in real time. This technique provides an easy access to the collected data for further analysis.